PENGARUH E-COMMERCE, PENGETAHUAN KEWIRAUSAHAAN DAN KEBERANIAN MENGAMBIL RISIKO TERHADAP MINAT BERWIRAUSAHA PADA SISWA PROGRAM KEAHLIAN AKUNTANSI SMK NEGERI 1 BANJARMASIN - Rara Gustiana; Ruslinda Agustina; Rizki Amalia Afriana (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this study was to empirically demonstrate the influence of e-commerce, entrepreneurial knowledge, and risk-taking on entrepreneurial interest among students in the accounting program at SMK Negeri 1 Ban`jarmasin. The research method was quantitative, with data collected through questionnaires distributed to 70 respondents. This study used SPSS version 26.00 as a statistical testing tool. The results showed that e-commerce variables influenced entrepreneurial interest, while entrepreneurial knowledge and risk-taking did not.